98.4k views
4 votes
Simplify.

1/2+(3/8−1/8)^2



Enter your answer, as a simplified fraction, in the box.
Please Hurry

User Seumasmac
by
4.8k points

2 Answers

0 votes

1/2+(3/8−1/8)^2

= 1/2+(2/8)^2

= 1/2+(1/4)^2

= 1/2 + 1/16

= 8/16 + 1/16

= 9/16

Answer

9/16

User Bluezen
by
5.4k points
3 votes

Answer:


(9)/(16) will be the answer.

Explanation:

The given expression in the question is
(1)/(2)+((3)/(8)-(1)/(8))^(2)

We will solve the parenthesis first.


((3)/(8)-(1)/(8))=((3-1))/(8)


=(2)/(8)


=(1)/(4)

Now the expression becomes
(1)/(2)+((1)/(4))^(2)

We further solve this expression


(1)/(2)+((1)/(4))^(2) =
((8+1))/(16)


=(9)/(16)

Answer will be
(9)/(16)

User Vincent J
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.